El capital relacional de las cooperativas de crédito en España: un estudio cualitativo de sus intangibles sociales mediante el análisis Delphi - Seguí-Mas, Elies; Server Izquierdo, Ricardo J. (REVESCO. Revista de Estudios Cooperativos, 2010)
Social Capital has constantly been used to explain the beneficial impact that some banking companies have on the economic and social development, especially for saving banks. Credit cooperatives, which are singular in our financial system, posses certain assets with their own features. Thus, corporate reputation, social relationships, interaction with public administration and media, and performance in social responsibility shape credit unions in such a way that it is worth to be studied. By means of Delphi analysis this work identifies the singularities of social capital in credit cooperatives. Among these specialties are remarkable the proximity and members’ participation (strength) and their reputation (weakness). Intangible social assets stand for a high value in credit cooperatives, especially with regard to the social responsibility (showing the strong commitment of these firms). In order to foster social capital in credit unions it is key to enhance communication policy, especially regarding the Education Fund. According to this argument, the saving banks' strategy could be considered as an example for the cooperative sector.
Keywords: Intangibles assets; Intellectual capital; Social capital; Knowledge management; Credit cooperatives; Corporate Social Responsibility; Corporate reputation